Crisis, Inequality, and Community Strength: Examining Dual Resilience in Tourism-Dependent Marginal Communities - I Gusti Ngurah Oka Widjaya; I Putu Andre Adi Putra Pratama; Ni Kadek Sri Mirayani; Putu Ade Wijana (Global Review of Tourism and Social Sciences, 2026)
This study investigates how poor households in the Tanjung Benoa Traditional Village in Bali navigated the socioeconomic collapse triggered by the Covid 19 interruption of tourism. Using a qualitative case study grounded in in-depth interviews, participant observation, and thematic analysis, the research introduces the concept of Dual Resilience to explain how communities endure chronic structural marginalisation while simultaneously responding to an acute crisis. The findings show that long-term tourism dependency, limited access to productive assets, and erosion of traditional livelihood spaces intensified the shock. Households adopted four interconnected strategies, namely subsistence economic diversification, limited occupational returns to fisheries, asset based coping, and collective cooperation embedded in customary social capital. Customary institutions emerged as the most effective support mechanism, while government and industry interventions were perceived as short term. The study advances a grassroots understanding of tourism vulnerability and highlights the need for more inclusive development pathways.